2023
DOI: 10.2147/nss.s340946
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Body Composition on Sleep and Its Relationship with Sleep Disorders: Current Insights

Abstract: Sleep is involved in many physiological processes and is essential for both physical and mental health. Obesity and sleep deprivation due to sleep disorders are major public health issues. Their incidence is increasing, and they have a wide range of adverse health-related consequences, including life-threatening cardiovascular disease. The impact of sleep on obesity and body composition is well-known, and many studies have shown an association between insufficient or excessive sleep duration and obesity, body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 171 publications
0
1
0
Order By: Relevance
“…OSAHS has emerged as a significant global health concern ( 2 ). Scholars have reported that the presence of excess fat in the upper airway contributes to an increased compliance and narrowing of the upper airway in individuals with obesity, which results in decreased neural reactivity of the upper airway during sleep and an elevated risk of airway collapse, ultimately leading to the development of OSAHS ( 3 ). Consequently, obesity emerges as a significant risk factor for OSAHS, necessitating further investigation into the impact of hormones encoded by obesity genes.…”
Section: Introductionmentioning
confidence: 99%
“…OSAHS has emerged as a significant global health concern ( 2 ). Scholars have reported that the presence of excess fat in the upper airway contributes to an increased compliance and narrowing of the upper airway in individuals with obesity, which results in decreased neural reactivity of the upper airway during sleep and an elevated risk of airway collapse, ultimately leading to the development of OSAHS ( 3 ). Consequently, obesity emerges as a significant risk factor for OSAHS, necessitating further investigation into the impact of hormones encoded by obesity genes.…”
Section: Introductionmentioning
confidence: 99%